Qualitative Development and Content Validation of the PROMIS Pediatric Sleep Health Items. Issue 5 (3rd September 2019) - Bevans, Katherine B.; Meltzer, Lisa J.; De La Motte, Anna; Kratchman, Amy; Viél, Dominique; Forrest, Christopher B.
ABSTRACT: Objective : To develop the Patient Reported Outcome Measurement Information System (PROMIS) Pediatric Sleep Health item pool and evaluate its content validity. Participants : Participants included 8 expert sleep clinician-researchers, 64 children ages 8–17 years, and 54 parents of children ages 5–17 years. Methods : We started with item concepts and expressions from the PROMIS Sleep Disturbance and Sleep Related Impairment adult measures. Additional pediatric sleep health concepts were generated by expert ( n = 8), child ( n = 28), and parent ( n = 33) concept elicitation interviews and a systematic review of existing pediatric sleep health questionnaires. Content validity of the item pool was evaluated with item translatability review, readability analysis, and child ( n = 36) and parent ( n = 21) cognitive interviews. Results : The final pediatric Sleep Health item pool includes 43 items that assess sleep disturbance (children's capacity to fall and stay asleep, sleep quality, dreams, and parasomnias) and sleep-related impairments (daytime sleepiness, low energy, difficulty waking up, and the impact of sleep and sleepiness on cognition, affect, behavior, and daily activities). Items are translatable and relevant and well understood by children ages 8–17 and parents of children ages 5–17. Conclusions : Rigorous qualitative procedures were used to develop and evaluate the content validity of the PROMIS Pediatric Sleep Health item pool. Once the item pool's psychometric properties are established, the scales will be useful for measuring children's subjective experiences of sleep.